A selection strategy in plant transformation based on antisense oligodeoxynucleotide inhibition. (8th March 2014) - Xie, Zhoupeng; Sundström, Jens F.; Jin, Yunkai; Liu, Chunlin; Jansson, Christer; Sun, Chuanxin
Summary Antisense oligodeoxynucleotide (asODN) inhibition was developed in the 1970s, and since then has been widely used in animal research. However, in plant biology, the method has had limited application because plant cell walls significantly block efficient uptake of asODN to plant cells. Recently, we have found that asODN uptake is enhanced in a sugar solution. The method has promise for many applications, such as a rapid alternative to time‐consuming transgenic studies, and high potential for studying gene functionality in intact plants and multiple plant species, with particular advantages in evaluating the roles of multiple gene family members. Generation of transgenic plants relies on the ability to select transformed cells. This screening process is based on co‐introduction of marker genes into the plant cell together with a gene of interest. Currently, the most common marker genes are those that confer antibiotic or herbicide resistance. The possibility that traits introduced by selectable marker genes in transgenic field crops may be transferred horizontally is of major public concern. Marker genes that increase use of antibiotics and herbicides may increase development of antibiotic‐resistant bacterial strains or contribute to weed resistance. Here, we describe a method for selection of transformed plant cells based on asODN inhibition. The method enables selective and high‐throughput screening for transformed cells without conferring new traits or functions to the transgenic plants. Due to their high binding specificity, asODNs may also find applications as plant‐specific DNA herbicides.